2017
DOI: 10.1002/pat.4129
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of antistatic high‐density polyethylene composites based on synergistic effect of graphene nanoplatelets and multi‐walled carbon nanotubes

Abstract: Graphene nanoplatelets are promising candidates for enhancing the electrical conductivity of composites. However, because of their poor dispersion, graphene nanoplatelets must be added in large amounts to achieve the desired electrical properties, but such large amounts limit the industrial application of graphene nanoplatelets. Multi-walled carbon nanotubes also possess high electrical conductivity accompanied by poor dispersion. Therefore, a synergistic effect was generated between graphene nanoplatelets and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Two strong peaks centered at 2θ = 21.38°a nd 2θ = 23.75°, corresponding to the (110) and (200) reflections of the HDPE orthorhombic phase, respectively, and two weak peaks centered at 2θ = 29.93° and 36.13°, corresponding to the (210) and (020) reflection planes, respectively, were clearly seen in the XRD pattern of pure HDPE. Similar HDPE peaks were observed by Sever and co-workers [22] and Wang and co-workers [23]. In the XRD patterns of the HDPE/GnP nanocomposites, the intensities of the peaks at 2θ ≈ 21.4° and 2θ ≈ 23.8° decreased with increasing GnP loading, while the intensities of the peaks at 2θ ≈ 26.5° and 2θ ≈ 54.6° increased.…”
Section: Characterizationsupporting
confidence: 83%
“…Two strong peaks centered at 2θ = 21.38°a nd 2θ = 23.75°, corresponding to the (110) and (200) reflections of the HDPE orthorhombic phase, respectively, and two weak peaks centered at 2θ = 29.93° and 36.13°, corresponding to the (210) and (020) reflection planes, respectively, were clearly seen in the XRD pattern of pure HDPE. Similar HDPE peaks were observed by Sever and co-workers [22] and Wang and co-workers [23]. In the XRD patterns of the HDPE/GnP nanocomposites, the intensities of the peaks at 2θ ≈ 21.4° and 2θ ≈ 23.8° decreased with increasing GnP loading, while the intensities of the peaks at 2θ ≈ 26.5° and 2θ ≈ 54.6° increased.…”
Section: Characterizationsupporting
confidence: 83%
“…Many studies have reported the benefits of adding graphene and its derivatives in the PE matrix to reinforce the thermal, electrical, and mechanical properties of the PE matrix. However, several reports have been reported on the preparation method of PE/graphene nanocomposites [ 10 , 11 , 12 , 13 , 14 ], the improvement in the interfacial interaction between PE-functionalized GNPs [ 15 , 16 , 17 , 18 , 19 ], the dispersion and alignment of graphene in the composite samples [ 20 , 21 ], and the construction of the hybrid network structures of graphene with other conductive fillers [ 10 , 22 , 23 ]. Although the GNPs size is an important factor, only a few works have studied the GNP’s size effect on the mechanical properties of High-Density Polyethylene (HDPE) nanocomposites [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that increasing GNP content improved the mechanical and thermal properties. When Wang et al [10] have studied the synergistic effect of GNP and carbon nanotube using high density polyethylene (HDPE) as a base polymer, it was found that the electrical properties improved. However, a slight decrease of mechanical properties was observed.…”
Section: Introductionmentioning
confidence: 99%